2022
DOI: 10.3389/fpls.2022.1047899
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of quantitative trait loci for flag leaf size in bread wheat (Triticum aestivum L.)

Abstract: Flag leaf size is a crucial trait influencing plant architecture and yield potential in wheat. A recombinant inbred line (RIL) population derived from the cross of W7268 and Chuanyu 12 was employed to identify quantitative trait loci (QTL) controlling flag leaf length (FLL), flag leaf width (FLW), and flag leaf area (FLA) in six environments and the best linear unbiased estimator (BLUE) datasets. Using a 55 K SNP-based genetic map, six major and stable QTL were detected with 6.33–53.12% of explained phenotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…For FLW, three major‐effect QTLs were identified: QFlw.uga‐1A on chromosome 1A and QFlw.uga‐2B.1 and QFlw.uga‐2B.2 on chromosome 2B. Several studies have identified QTLs related to flag leaf traits on chromosomes 1A and 2B (Chen et al., 2022; Du et al., 2022; K. Liu et al., 2018; Salarpour et al., 2020; Q. Wu et al., 2016; X. Yan et al., 2020; Yang et al., 2016). However, none of these reported QTLs co‐localized with our QTLs QFlw.uga‐1A and QFlw.uga‐2B.2 (Table S7), suggesting them to be novel loci for FLW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For FLW, three major‐effect QTLs were identified: QFlw.uga‐1A on chromosome 1A and QFlw.uga‐2B.1 and QFlw.uga‐2B.2 on chromosome 2B. Several studies have identified QTLs related to flag leaf traits on chromosomes 1A and 2B (Chen et al., 2022; Du et al., 2022; K. Liu et al., 2018; Salarpour et al., 2020; Q. Wu et al., 2016; X. Yan et al., 2020; Yang et al., 2016). However, none of these reported QTLs co‐localized with our QTLs QFlw.uga‐1A and QFlw.uga‐2B.2 (Table S7), suggesting them to be novel loci for FLW.…”
Section: Discussionmentioning
confidence: 99%
“…For FLW, three major-effect QTLs were identified: QFlw.uga-1A on chromosome 1A and QFlw.uga-2B.1 and QFlw.uga-2B.2 on chromosome 2B. Several studies have identified QTLs related to flag leaf traits on chromosomes 1A and 2B (Chen et al, 2022;Du et al, 2022;K. Liu et al, 2018;Salarpour et al, 2020;Q.…”
Section: Novelty Of High-confidence Major-effect Qtls and Their Candi...mentioning
confidence: 99%
“…The yield of wheat is primarily determined by three components: grain number per spike (GNS), grain weight, and spike number [ 6 , 7 ]. Previous studies have shown that GNS significantly impacts wheat grain yield more than grain weight [ 8 10 ]. In wheat breeding programs, high yield is primarily achieved by increasing GNS rather than grain weight [ 11 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reasoned that conserving the energy invested in roots during times of stress could help explain the greater shoot growth and yields of some genotypes compared with others (Chimungu et al, 2014a, b; Saengwilai et al, 2014a, b; Gao and Lynch, 2016). However, the characteristics of an efficient root system and the value of particular root traits and their associated QTLs (Ober et al, 2021; Halder et al, 2023; Li et al, 2023) are not necessarily beneficial in all conditions. Under different stresses, a larger root system might be more efficient even though it requires a greater proportion of the plant's resources to develop and maintain.…”
Section: Introductionmentioning
confidence: 99%